Effects of Different Drying Methods on Total Flavonoids Content and Antioxidant Activity of Hawthorn - Shihao LOU; Xiaojing SUN; Dandan LI; Chenchen ZHAO; Jianhua XIU (Shipin gongye ke-ji)
To explore the effect of different drying methods on total flavonoids components and content and antioxidant activity of hawthorn, three drying techniques were selected including hot air drying, vacuum freeze drying and hot air combined liquid nitrogen drying. The total flavonoids yield, total flavonoids fraction and content of hawthorn powder samples were determined using sodium nitrite-aluminum nitrate-sodium hydroxide colorimetric method and high-performance liquid chromatography (HPLC). The antioxidant capacity of each sample was assessed using the free radical scavenging ability experiment. The results showed that the color difference values of hawthorn powder samples dried by hot air drying, vacuum freeze drying and hot air combined liquid nitrogen drying were 20.60, 17.70 and 20.05, respectively. The yields of hawthorn total flavonoids were 64.59, 71.48 and 60.77 mg/g, respectively. The scavenging ability against DPPH radical was 19.56%, 30.14%, and 18.50%, respectively. The free radical scavenging rates for ABTS+ were 51.81%, 75.08%, and 48.68%, respectively. And the hydroxyl radical scavenging rates were 48.98%, 55.77%, and 36.04%, respectively. The total flavonoids yield and antioxidant activity were the highest in the vacuum freeze dried hawthorn powder samples, which were significantly different from those extracted by other drying methods (P<0.05). The qualitative and quantitative analysis of total flavonoids of hawthorn by high performance liquid chromatography showed that the total flavonoids obtained by the three methods contained rutin, hyperoside, myricetin, quercetin, apigenin, isorhamnetin, but their contents were different, and the total flavonoids content of the vacuum freeze dried samples was the highest, reaching 308.65 mg/g, which was significantly different from that of the other samples (P<0.05). In addition to this, there was also a linear relationship between the three antioxidant modes and the content of the six components. In conclusion, vacuum freeze drying treatment of hawthorn is a recommended method for extracting total flavonoids from hawthorn, which can effectively reduce the effect of processing on the content and antioxidant activity of the total flavonoids from hawthorn.